2017
DOI: 10.1039/c7nr04922f
|View full text |Cite
|
Sign up to set email alerts
|

Improved catalytic activity of Mo1−xWxSe2 alloy nanoflowers promotes efficient hydrogen evolution reaction in both acidic and alkaline aqueous solutions

Abstract: Layered transition metal dichalcogenides are noble-metal free electrocatalysts for the hydrogen evolution reaction (HER). Instead of using the common hydrothermal synthesis, which requires high pressure and temperature, herein a relatively simple and controlled colloidal synthesis was used to produce an alloy of MoWSe with nanoflower morphology as a model system for the electrocatalysis of hydrogen evolution in both acidic and alkaline environments. The results show that MoWSe alloys exhibit better catalytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 37 publications
1
62
0
Order By: Relevance
“…Introducing impurity atoms into TMDs can improve the adsorption of H atoms on the surrounding S sites of the dopants, which enhances their HER activity . The synergistic effect of 2D TMD alloys also contributes to enhancing the HER activity; for example, Mo 1− x W x Se 2 and MoS 2(1− x ) Se x show better HER activity than their binary compounds . Besides the above applications, 2D doped TMDs have promise to be applied in some emerging areas such as spin electronic devices.…”
Section: D Doped Transition‐metal Dichalcogenidementioning
confidence: 99%
“…Introducing impurity atoms into TMDs can improve the adsorption of H atoms on the surrounding S sites of the dopants, which enhances their HER activity . The synergistic effect of 2D TMD alloys also contributes to enhancing the HER activity; for example, Mo 1− x W x Se 2 and MoS 2(1− x ) Se x show better HER activity than their binary compounds . Besides the above applications, 2D doped TMDs have promise to be applied in some emerging areas such as spin electronic devices.…”
Section: D Doped Transition‐metal Dichalcogenidementioning
confidence: 99%
“…The crystallographic structure of most TMDCs is similar, and conveniently, the material properties can be significantly modified depending on the size, polarizability and charge of both constituting elements. In MoSe 2 , each layer of Mo is sandwiched between two layers of hexagonally close‐packed Se atoms, and the atomic layers are stacked by weak van‐der‐Waals interactions . It is already well established that active sites, intrinsic activity and conductivity govern the electrocatalytic HER activity .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many strategies were employed to improve the performance of MoSe 2 . In addition to directly creating edge‐rich morphology, forming additional active catalytic sites by doping of the TMDC with other transition metals has gained much attention . High affinity of Co to the saturation of the edges of layered d ‐metal dichalcogenides is well established and is extensively applied in catalysis .…”
Section: Introductionmentioning
confidence: 99%
“…It is against this background that efforts are currently being dedicated to further modify the MoS2 structures with the aim of improving performance by increasing the density of their catalytic sites either by creating defects, [7][8][9] modifying the morphology or by doping with other transition metals. [2][3][10][11] Another approach is to combine MoS2 with other materials and produce hybrids with improved electrical conductivity, 12 more active basal planes, 13 or improved photocatalytic activity. [14][15] Recently, a study exploring the thickness dependence (number of layers) of MoS2 electrocatalysts showed a significant improvement in the catalytic activity for HER with decreasing number of layers.…”
Section: Introductionmentioning
confidence: 99%